The Influence of Islamic Moral Values on the Students’ Behavior in Aceh - Nuriman, Nuriman; Fauzan, Fauzan (Dinamika Ilmu, 2017)
This study shows the influence and relationship of Islamic moral values to the students’ behavior in Aceh Province. Learning Objects are the moral values of Islam achieved in learning in high school and vocational institutions that are assumed to affect the students’ behavior. The quantitative methods used in this study and was running by SPSS program. Data analysis using MRPI Likert Scale instrument. The data were taken from the students in the school totaling of 191 samples. The t-test and r test are used to analyze data from this research sample. The study found that Islamic moral values significantly correlated with the behavioral student at the level; [r (98) = 2.186 P <0.05]. The mean difference scores is 4.7 percent at the level (eta2 = 0.0047) and it was explained by the mean score at the rate (48.05: 5.56), and the student behavior is described with the average score (45.7: 5.12). In which a relational to behavioral variables (Y) with horizontal and vertical Islamic moral values (X1 and X2). This findings represented by multiple regression test (r) which score of 12.28 percent. Therefore, the study found significant differences between male and female student and positively related to student behavior. These findings have explained the pattern of relationships and the influence of moral values on students and implications for future research practice due to Islamic moral values and behaviral students.